Drought-induced and seasonal variation in carbon use efficiency is associated with fungi:bacteria ratio and enzyme production in a grassland ecosystem. (April 2021) - Ullah, Mohammad Rahmat; Carrillo, Yolima; Dijkstra, Feike A.
Abstract: Drought causes alterations in the abundance of fungi and bacteria in soil, which could affect community level microbial carbon use efficiency (CUE) and the capacity to store C in soil. We examined drought effects (implemented with rainout shelters) on microbial community composition, enzyme activity, and CUE during a dry summer and wet winter in a seminatural grassland in Australia. Drought caused small increases in CUE in both dry and wet seasons. However, CUE was much higher in the wet winter than in the dry summer. Seasonal variation in CUE were related to changes in microbial community composition where CUE was negatively associated with fungal abundance and fungi:bacteria ratio. Moreover, CUE was negatively related to β-glucosidase and peroxidase activity, suggesting that increased abundance of fungi that invest more C in the production of these enzymes resulted in the reduced CUE. Overall, our results suggest that seasonal variation in CUE could be driven by changes in microbial community composition, and that seasonal effects are larger than effects caused by drought in this grassland. Graphical abstract: Image 1 Highlights: Drought caused small increases in CUE across season. CUE was lower in summer with greater fungal dominance. Higher fungi:bacteria ratios were associated with reduced CUE. Higher enzyme activity was associated with reduced CUE.